PROMOTION OF NON-SUBJECT NOUN PHRASE TO SUBJECT IN CLAUSE OF SABU LANGUAGE, SABU RAIJUA REGENCY, EAST NUSA TENGGARA PROVINCE - Sukendra, I Nyoman; Artawa, Ketut; Mbete, Aron Meko; Kardana, I Nyoman (e-Journal of Linguistics, 2013)
This study is a descriptive-qualitative one exploring the relation of non subject THAT was promoted to the slot of subject. From the syntactic point of view, two informants were considered adequate in the present study. The reason was that the Sabu language ‘Bahasa Sabu (hereinafter referred to as BS), as a langue, was homogenous in nature. The data needed were collected through observation and interview. The words, phrases, clauses and sentences focused on the topic of the study were note taken. In addition, the data were also collected by recording the speeches made by the BS speakers and the informants using a tape recorder and an electronic recorder. In this manner, it was possible to obtain as many data as possible. From the analysis, it was found that the clausal construction in BS could promote the non subject NP to the subject as the original subject could not be deleted. The other finding was that the promotion of the non-subject NP could be promoted to the slot of subject in the transitive and intransitive clauses. The clausal construction which could allow the promotion of the non-subject NP to the clausal construction was the clausal construction which had semantic roles as the MOTION, AFFECT, and CORPOREAL verbs. The clausal construction which could not allow the non-subject NP to be promoted to the subject was the instrumental clausal construction whose verb was realized by the verb hernabi ‘tutup’ [close].
Keywords: semantic role, promotion of non subject NP, slot of subject, transitive, intransitive.